Lives in Welfare States: Life Courses, Earnings Accumulation, and Relative Living Standards in Five European Countries - Fasang, Anette Eva; Andrade, Stefan Bastholm; Bedük, Selçuk; Buyukkececi, Zafer; Karhula, Aleksi (University of Chicago Press, 2026)
How do work and family life courses differ in welfare states with varying emphasis on the state, market, and family for welfare provision? The authors compare life courses until midlife in Denmark, Finland, the United Kingdom, former West Germany, and reunified Germany. Longitudinal life course analyses using administrative and survey data support three main conclusions. First, young adults who accumulate high earnings experience similar life courses in all countries. In contrast, typical life courses of low earners, particularly their family lives, differ widely between European welfare states. Second, constellations of decommodifying, familizing, and defamilizing policies shape cross-national differences in typical low-earning life courses, their primary sources of economic support, and relative living standards. Third, women are most likely to experience low-earning life courses in familizing welfare states (Germany, United Kingdom) compared to relative gender equality among low-earning life course types in welfare states that combine high defamilization and decommodification (Denmark, Finland).